Saccharomyces cerevisiae pms2 mutations are alleles of MLH1, and pms2-2 corresponds to a hereditary nonpolyposis colorectal carcinoma-causing missense mutation. - Jeyaprakash, A (1996)
A number of mutant Saccharomyces cerevisiae strains having phenotypes consistent with defects in DNA mismatch repair have been described, but not all have been extensively characterized. In this study we demonstrate that the pms2-1 and pms2-2 alleles arise from missense mutations in the MLH1 gene which inactivate MLH1. One of these alleles, pms2-2, causes the same amino acid substitution in a highly conserved region of the known MutL homologs as that caused by a proposed missense mutation observed in a Swedish hereditary nonpolyposis colorectal carcinoma kindred. This observation supports the functional significance of missense mutations found in hereditary nonpolyposis colorectal carcinoma kindreds and indicates that in some cases S. cerevisiae can serve as a useful model system for the analysis of such mutations.